Family Physician Financing: Developing versus Developed countries - Fardid, Mozhgan; Jafari-Sirizi, Mehdi; Vosoogh-Moghaddam, Abbas; Ravaghi, Hamid (Revista Publicando, 2018)
Considering the role of family physician in rising public access to general practice under a referral system on one hand and its impact on the reduction of health cost on another hand, we compare family physician in ten countries with the following inclusion criteria: different regions of WHO, a well-known or specific health financing, at least a country similar to Iran in terms of socioeconomic situation and Gross Domestic Production (GDP), at least one of the countries in the list of 1404 Iran Vision Document, and the availability of data. The required data were gathered through valid databases, important documents as well as the famous website with the focus on financial function of family physician. Finally, data was analyzed by comparative tables. The findings revealed that most resources in selected countries are collected from public revenues. Besides, family physician is not funded separately and all countries finance family physician under the primary health care. The results of this study also showed that purchasing family physician services in different countries is based on contracts and its payment mechanism is a mix of salary, capitation, bonus, fee for service or pay for payment, however, reimbursement to Iranian urban family physicians is mostly through capitation. The experiences of different countries in the implementation of family physician shows that the mechanisms of collecting resources is different across different countries due to their various context. This study suggests that more emphasize on public resources and suitable pooling may be a good solution to improve family physician financing.